Lumbar hernia- A case report (Albayan Scientific Journal, 2023)
Lumbar hernia is uncommon type of abdominal hernia, only rare cases reported in the literature. It is commonly misdiagnosed as lipoma, fibroma or muscle strain. It usually affects 30 to 60 years of age in the adult group with a male predominance, although it can occur at almost any age. It stated in the literature to be more common on the left side and in the inferior lumbar triangle of petit. In our case report we discus case of Libyan male of 21 years old, presented with right inferior lumbar hernia. No specific abdominal pain, he complained from right flank swelling The diagnosis was clinically  and confirmed intra-operatively and the hernia was repaired using synthetic mesh.  Six months Follow up after the operation shows no recurrence. It was a case of primary spontaneous lumbar hernia in the inferior lumbar triangle. Clinical findings were correlated to reach the diagnosis. We also highlight the types, the process of diagnosis and the surgical repair of lumbar hernias. Because of high risks of incarceration in lumbar hernias demand a relatively fast elective repair. The use of a mesh is recommended, and the surgical approach should be tailored to individual patient characteristics and risk factors.
Keywords: Lumbar Hernia; posterior abdominal hernia; lipoma; fibroma; synthetic mesh; polypropylene mesh.